Modulating TRPV1 and TRPA1 channels: a viable strategy for treating asthma using Chinese herbal medicines - Yao, Xiang; Zhang, Xuejian; Cui, Tao; Jian, Meiling; Wu, Hao; Wu, Chunjie; Tao, Feiyan (Frontiers in Pharmacology, 2025)
Asthma represents a significant global health challenge, imposing a substantial burden on society worldwide. Over the past decades, the development of asthma medications has significantly reduced asthma-related mortality. However, current pharmacological treatment regimens have not yet demonstrated the capacity to induce a durable remission of asthma. Transient receptor potential channels, specifically vanilloid receptor 1 (TRPV1) and ankyrin 1 (TRPA1), are polymodal sensory channels extensively distributed in the lungs and represent promising therapeutic targets for asthma. Increasing evidence suggests that Chinese herbal medicines (CHM) exert beneficial effects in asthma treatment by modulating TRPV1/TRPA1. Therefore, this study systematically analyzed 134 articles covering the pathogenesis of asthma, current treatment strategies, the role of TRPV1/TRPA1 in asthma, and the modulation of TRPV1/TRPA1 by Chinese herbal medicines in asthma. In summary, our review comprehensively elaborates on how CHM modulates TRPV1/TRPA1 channels to alleviate pulmonary inflammation. These findings provide viable options for asthma drug discovery and establish the foundation for developing effective CHM-based therapeutics.